Resource Scheduling in Cloud: A Comparative Study - Dewangan, Bhupesh Kumar; Agarwal, Amit; Venkatadri, M; Pasricha, Ashutosh (International Journal of Computer Sciences and Engineering, 2018)
Cloud computing provides a platform where services are facilitating to the cloud user through the web, either free of cost or lease base. The cloud user and demands are increasing, due to this large number of service request are submitting to the cloud service provider. To manage those service requests, scheduling plays a key role for the service provider to manage their resource and operational cost. In this paper, the state of art survey has been carried out on recent developments in resource scheduling algorithms for cloud computing. This paper provides the comparative analysis of all the surveyed algorithms in terms of different performance metrics. The observation of the survey provides some research gaps to improve the efficiency of the existing resource management system.